Monitoring the Secretory Behavior of the Rat Adrenal Medulla by High-Performance Liquid Chromatography-Based Catecholamine Assay from Slice Supernatants - De Nardi, Frédéric; Lefort, Claudie; Bréard, Dimitri; Richomme, Pascal; Legros, Christian; Guérineau, Nathalie C. (Frontiers in Endocrinology, 2017)
Catecholamine secretion from the adrenal medullary tissue is a key step of the adaptive response triggered by an organism to cope with stress. Whereas molecular and cellular secretory processes have been extensively studied at the single chromaffin cell level, data available for the whole gland level are much scarcer. We tackled this issue in rat by developing an easy to implement experimental strategy combining the adrenal acute slice supernatant collection with a high performance liquid chromatography-based epinephrine and norepinephrine assay. This technique affords a convenient method for measuring basal and stimulated catecholamine release from single acute slices, allowing thus to individually address the secretory function of the left and right glands. Our data point that the two glands are equally competent to secrete epinephrine and norepinephrine, exhibiting an equivalent epinephrine:norepinephrine ratio, both at rest and in response to a cholinergic stimulation. Nicotine is however more efficient than acetylcholine to evoke norepinephrine release. A pharmacological challenge with hexamethonium, an α3-containing nicotinic acetylcholine receptor antagonist, disclosed that epinephrine- and norepinephrine-secreting chromaffin cells distinctly expressed α3 nicotinic receptors, with a dominant contribution in norepinephrine cells. As such, beyond the novelty of catecholamine assays from acute slice supernatants, our study contributes at refining the secretory behavior of the rat adrenal medullary tissue, and opens new perspectives for monitoring the release of other hormones and transmitters, especially those involved in the stress response.